The Effect of Relational Embeddedness, Absorptive Capacity, and Learning Orientation on SMEs’ Competitive Advantage - Wu, Guo-Song; Peng, Michael Yao-Ping; Chen, Zhong; Du, Zongmin; Anser, Muhammad Khalid; Zhao, Wen-Xuan (Frontiers in Psychology, 2020)
The combination of external new knowledge and organizational capability has become a cornerstone in the knowledge and labour intensive enterprises. Sources of Knowledge acquisition are among the most valuable resources that an internationalized firm can utilize for competitive advantage. However only few research have addressed this phenomenon between knowledge sources and competitive advantage by adopting mainly a qualitative approach. Based on contextual nature of resource-capability-competitive, this implies that organizational capability plays a transformation role in leveraging external new knowledge to create maximized enterprise value. Absorptive capacity has long been a critical construct in organizational studies. Yet, limited research exists on absorptive capacity in an international context. This study focuses on relational embeddedness as potential drivers of absorptive capacity which is moderated by learning orientation, and investigate the mediating effect that potential and realized absorptive capacity to absorb and process knowledge has on international competitive advantage. To gain insights from the global economy, 211 small to medium enterprises from global enterprises were analyzed. Via the Partial Least Square-Structural Modelling the relationships among relational embeddedness, potential and realized absorptive capacity, and competitive advantage were measured. The survey results suggest that relational embeddedness positively influences potential and realized absorptive capacity with moderating effect of learning orientation. Potential and realized absorptive capacity have full mediating effect between relational embeddedness and competitive advantage. The article concludes with a discussion of implications for research and practice.